Length of Neuromuscular Re-education Therapy and Growth Parameters in Premature Infants - Leone, Mariana; Alsofrom, Jessica; Kane, Megan; Laryea, Sarah; Abdelatif, Dinan; Mohamed, Mohamed A. (American Journal of Perinatology, 2020)
Objective Neuromuscular re-education (NMRE) therapy including bracing, containment, facilitation techniques, joint compression, weight (WT) bearing, and myofascial release has been shown to improve neurodevelopmental maturation in premature infants. This study aimed to examine the association of NMRE with growth parameters including WT and length (L) at 36 weeks postmenstrual age (PMA) and at discharge.Study Design We analyzed data of infants <34 weeks gestational age (GA) or <1,800 g birth weight (BW) to examine the association of NMRE with growth parameters using correlation coefficient analysis. The effect of potential confounders was examined using multilinear regression models.Results Study includes 253 premature infants. Average GA was 300/7 weeks (±23/7) and BW was 1,315 g (±416), 49.8% were females and 65% were African Americans. NMRE has inverse correlation with WT at birth and at 36 weeks PMA, −0.66 (<0.001) and −0.21 (<0.001), respectively, but not at the time of discharge. NMRE has direct correlation with change in WT from birth to 36 weeks PMA and time of discharge, 0.50 (<0.001) and 0.62 (<0.001), respectively, and from the time of starting therapy to 36 weeks PMA or discharge, 0.25 (<0.001) and 0.51 (<0.001), respectively. There was no negative correlation between NMRE with daily WT gain from birth to 36 weeks PMA or to discharge, −0.05 (0.43) and −0.07 (0.23), respectively, or from the time of starting therapy to 36 weeks PMA, −0.09 (0.14). There was an inverse correlation between NMRE with average WT gain per day from the time of starting therapy to discharge, −0.26 (<0.001), Similar findings were found examining the correlation between NMRE and changes in L. Multilinear regression analysis examining the relationship while controlling for GA, BW, sex, and race; socioeconomic variables; and concurrent massage therapy and sensory integration revealed similar results.Conclusion NMRE, aimed to enhance neurodevelopmental outcomes of premature infants, may not have a negative impact on their physical growth.Key Points
Keywords: neuromuscular re-education therapy; premature infants; neurodevelopmental maturation; physical growth